2007
DOI: 10.1124/mol.107.041640
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility of Helix VI Is Essential for Substrate Permeation of the Human Apical Sodium-Dependent Bile Acid Transporter

Abstract: The present study characterizes the methanethiosulfonate (MTS) inhibition profiles of 26 consecutive cysteine-substituted mutants comprising transmembrane (TM) helix 6 of the human apical Na ϩ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…Note that substrate binding and translocation does not require fulfillment of all five features simultaneously. As mapped to the protein, our studies have putatively identified residues satisfying the first two features (21,(23)(24)(25); studies with ASBT orthologs and paralogs corroborate these assignments (26,27,37). However, there has been minimal progress toward identification of apolar residues involved in hydrophobic substrate-protein interactions.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Note that substrate binding and translocation does not require fulfillment of all five features simultaneously. As mapped to the protein, our studies have putatively identified residues satisfying the first two features (21,(23)(24)(25); studies with ASBT orthologs and paralogs corroborate these assignments (26,27,37). However, there has been minimal progress toward identification of apolar residues involved in hydrophobic substrate-protein interactions.…”
Section: Discussionmentioning
confidence: 53%
“…Using this approach, we have thus far identified putative portions of the substrate permeation path, including specific protein regions likely interacting or binding substrates of ASBT (21)(22)(23)(24). Here, we focused on the highly conserved, large extracellular loop 1 (EL1) spanning 27 amino acids (Val-99 -Ser-126) based on the following rationale.…”
mentioning
confidence: 99%
“…18) A difference in residues at position 294 and 295 in mammalian SLC10A2/Slc10a2 has been reported to determine sensitivity to the inhibitor, ((3R,5R)-3-butyl-3-ethyl-5-phenyl-2,3,4,5-tetrahydro-1,4-benzothiazepine 1,1-dioxide (known as 2164U90). 29) [30][31][32] In spite of such extensive research, it is still unclear how SLC10A2 interacts and transports its substrates, and most of the residues proposed to interact with bile acids have not been mapped in the highly conserved region (except for Asp 122 and Asp 124 ). The regular function of SLC10A2 is important for reabsorption of bile acids in the ileum, and surgical elimination of this function increased colonic tumorigenesis in the rat fed deoxycholic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Further, ASBT constitutes a pharmacologic target for improving oral drug bioavailability (5-7) as well as hypocholesterolemic agents, because cholesterol metabolism is induced upon bile acid depletion (8,9). To elucidate the structure-function relationship of ASBT, our laboratory has previously employed cysteine scanning mutagenesis and site-directed alkylation techniques (10,11) to determine structural requirements for substrates and their turnover (11)(12)(13)(14)(15)(16). We demonstrate that residues lining TM6 (12) and TM7 (15) participate in substrate recognition and protein entry from the exofacial matrix, while the cytosolic half of TM3 mediates substrate release into the cytosolic milieu (14), putatively in conjunction with TM4 (18).…”
mentioning
confidence: 99%
“…To elucidate the structure-function relationship of ASBT, our laboratory has previously employed cysteine scanning mutagenesis and site-directed alkylation techniques (10,11) to determine structural requirements for substrates and their turnover (11)(12)(13)(14)(15)(16). We demonstrate that residues lining TM6 (12) and TM7 (15) participate in substrate recognition and protein entry from the exofacial matrix, while the cytosolic half of TM3 mediates substrate release into the cytosolic milieu (14), putatively in conjunction with TM4 (18). Moreover, the extracellular loop (EL) 1 (13) and EL3 (16) regions mediate initial bile acid and sodium recognition and binding and may facilitate movement of ligands in solvent-accessible pockets situated deeper into the protein core, for ultimate translocation along membrane-spanning domains.…”
mentioning
confidence: 99%